Pengaruh Phsycal Distancing Dan Social Distancing Terhadap Produktivitas Kerja Karyawan Pada PT “X” Cikarang Bekasi - Anita Novialumi (Peneliti.net, 2021)
This study used a descriptive qualitative approach, with the objectives of this study were 1). To find out whether the social distancing and social distancing policies are carried out within the company, 2). To determine the effect of social distancing on employee work productivity, 3). To determine the effect of psychological distancing on employee work productivity. Based on the facts that have occurred, the spread of the corona virus has spread throughout the world, including Indonesia. The outbreak of this virus has an impact on various sectors, such as the economic sector, many business actors have decreased their productivity, to avoid the spread of the corona virus which is more widespread in the economic sector or work environment, the government has been forced to take policies such as physical distancing (restriction of physical contact), social distancing. (social restrictions), work from home (work from home), always wear a mask and always check body temperature when entering the workspace, even though this government policy has and affects the results of company productivity, but in current conditions government policy is a policy that is positive in breaking the chain of spread and expansion of the corona virus.